Parate Execution After the Indonesian Constitutional Court’s Judicial Review of Fiducia Law and Mortgage Law - Wardani, Kusuma (Global Legal Review, 2024)
According to the Law No. 42 of 1999 on Fiducia Security (“Fiducia Law”) as well as the Law No. 4 of 1996 on Mortgage, if there is a breach of fiduciary guarantee and mortgage rights, the secured creditors can undertake a parate execution, as the expedient, simple and cost-efficient method by means of a public auction. However, the Indonesian Constitutional Court’s (MKRI) Decision Number 18/PUU-XVII/2019 has interpreted Parate Execution of Fiduciary Guarantee must firstly obtain the debtor’s consent that a breach has indeed occurred and the voluntarily surrenders of the guarantee object to the creditor. On the other hand, in the Decision No. 21/PUU-XVIII/2020, MKRI did not define the same process for Parate Execution of Mortgage Rights. From the substance point of view, the two MK verdicts provide a different interpretation of the principle of “pacta sunt servanda” and fiducia security. This has caused the execution of Fiduciary Guarantee becomes not easy, expedient and cost efficient any longer. This normative research attempts to analyse the legal and economic impact of the two verdicts and their implementation from a law and justice perspective. The results show the need of consistency in the implementation of Parate Execution for both. This means that an agreement regarding the existence of a breach is not required. In addition, if the debtor does not voluntarily surrender the guarantee object, then the creditor by law reserves the rights to seize the object. Arguably, it is necessary to amend the Fiducia Law in accordance with the MKRI’s Decisions, in line with the general principles of security in parallel with the principles of justice, legal certainty and utility.